Coffee Bean Inventory Analysis Using EOQ Method at Lujo Coffee - Arilla Syah, Ardhi; Asngadi, Asngadi; Kaseng, Saharuddin; Dwiwijaya, Kadek Agus (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the management of coffee bean inventory at Lujo Kopi through the application of the Economic Order Quantity (EOQ) method, with the primary objective of optimizing inventory costs and improving efficiency in small-scale business operations. Methodology: A descriptive quantitative approach was employed by collecting one year of historical data covering raw material demand, ordering costs, and holding costs. The EOQ formula was then applied to calculate the optimal order quantity, order frequency, safety stock, reorder point, and total inventory cost. Results: The analysis indicated that the EOQ method provides a more efficient outcome compared to the conventional system previously applied. The optimal order quantity was found to be 86 kg with an order frequency of seven times per year. Total inventory costs decreased significantly from Rp. 7,320,000 to Rp. 3,740,232, highlighting substantial efficiency improvements. Conclusion: The findings confirm that the EOQ method offers a systematic and effective approach to managing raw material inventory, ensuring cost efficiency and more reliable supply management for UMKM. Limitations: The scope of this study is limited to one type of raw material and one case of UMKM, thereby reducing the generalizability of the results to other industries or business types. Contribution: This research provides valuable practical insights for UMKM, demonstrating the importance of data-driven decision-making in inventory management and encouraging wider adoption of EOQ-based approaches to achieve sustainable efficiency.